Five metal elements homeostasis-related genes in Synechogobius hasta: Molecular characterization, tissue expression and transcriptional response to Cu and Fe exposure. (September 2016) - Chen, Feng; Luo, Zhi; Fan, Yao-Fang; Wu, Kun; Pan, Ya-Xiong; Liu, Xu; Zhang, Li-Han; Song, Yu-Feng
Abstract: Two isoforms of Cu transporter (CTR1 and CTR2) and metallothionein (MT1 and MT2), and divalent metal ion transporter 1 (DMT1) were cloned and characterized in Synechogobius hasta, respectively. The protein sequences of S. hasta CTRs possessed two methionine-rich regions (MxM and MxxxM) and three transmembrane regions. At the C-terminus, CTR1 contained a sequence of conserved cysteine and histidine residues (HCH), while CTR2 did not contain the conserved sequence. The protein sequence of S. hasta DMT1 possessed all the characteristic features of DMT1, including twelve conserved hydrophobic cores of transmembrane domains. The protein sequences of S. hasta MTs were highly conserved in the total number of cysteine residues and their locations. mRNA of the five genes were expressed in a wide range of tissues but the levels were relatively higher in the liver. Cu exposure tended to up-regulate the mRNA expressions of CTR2, DMT1, MT1 and MT2. However, Fe down-regulated the Cu-induced increase of CTR2 and DMT1 mRNA levels. For the first time, our study cloned and characterized CTR1, CTR2, DMT1, MT1 and MT2 genes in S. hasta and determined their tissue-specific expression, and also the transcriptional change by Cu and Fe exposure, which shed new light on the CuFe relationship and help to understand the basic mechanisms of Cu and Fe homeostasis in fish. Highlights: The full-length cDNA sequences of five metal elements homeostasis-related genes were firstly characterized. mRNA of the five genes were expressed in a wide range of tissues but the levels were relatively higher in the liver. Cu exposure tended to up-regulate the mRNA expressions of CTR2, DMT1, MT1 and MT2. Fe down-regulated the Cu-induced increase of CTR2 and DMT1 mRNA levels.